Forest dependence and participation in CPR management: empirical evidence from forest co-management in Malawi - Jumbe, C.B.L.; Angelsen, A. (2007)
The authors develop an endogenous sample selection model to investigate how forest dependence influences a household's decision to participate in forest co-management program. Using data from Chimaliro and Liwonde forest reserves in Malawi, The authors find that where forests primarily have a gap filling or safety net role in Chimaliro, high forest dependency induces higher rates of participation. However, with more commercial forest uses and a more heterogeneous social context as in Liwonde, high forest dependency reduces the incentives for participation. The findings point to the need to design parallel interventions alongside the forest co-management program in order to provide supplementary income sources to participants and increase the incentives for participation.